2011
DOI: 10.1002/jwmg.99
|View full text |Cite
|
Sign up to set email alerts
|

The role of tower height and guy wires on avian collisions with communication towers

Abstract: Every year an estimated 4–5 million migratory birds collide with communication towers in the United States. We examined the relative risks that tower support systems and tower height pose to migrating and other birds. We collected data comparing tower support systems (guyed vs. unguyed) and tower height categories in Michigan during 20 days of the peak of songbird migration at 6 towers in September–October 2003, 23 towers in May 2004, 24 towers in September 2004, and 6 towers in both May and September 2005. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 8 publications
0
18
2
Order By: Relevance
“…Contrary to expectations based on previous studies (Gehring et al. , Boves and Belthoff ), we found no effect of season on searcher efficiency. However, unlike previous research, our survey areas exhibited minimal seasonal changes in vegetation cover, and further, we did not perform observer detection trials in winter when conditions influencing detectability may have differed more dramatically.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to expectations based on previous studies (Gehring et al. , Boves and Belthoff ), we found no effect of season on searcher efficiency. However, unlike previous research, our survey areas exhibited minimal seasonal changes in vegetation cover, and further, we did not perform observer detection trials in winter when conditions influencing detectability may have differed more dramatically.…”
Section: Discussioncontrasting
confidence: 99%
“…This observer detection bias has been systematically assessed for many mortality sources and may increase with extensive vegetative cover, poor light conditions, inclement weather, and observer fatigue or inattentiveness (Gehring et al. , Korner‐Nievergelt et al. , Mathews et al.…”
Section: Introductionmentioning
confidence: 99%
“…Large, heavy-bodied species such as swans, pelicans, herons, and cranes are generally thought to be more susceptible to transmission line collisions than smaller, more maneuverable species (APLIC 2012). Nocturnal migrants have not been well studied, but also may be susceptible, particularly within migration corridors (Rogers et al 2014), and especially in light of their susceptibility to collision with other types of tall anthropogenic structures (Drewitt and Langston 2008, Kerlinger et al 2010, Gehring et al 2011. Relatively small duck and grouse species are also vulnerable to collision because of their high flight speed, low altitude, and flocking flight, in which the view of upcoming obstacles is obscured by leading birds (APLIC 1994, Bevanger andBrøseth 2004).…”
Section: Power Linesmentioning
confidence: 99%
“…A review of wind turbine‐related bat mortality found no studies documenting bat carcasses at the shorter meteorological towers (Arnett et al 2008). All things being equal, shorter unlit and unguyed towers seem to kill fewer or no birds, but there is still a need for more data on short towers to use in the meta‐analyses of tower studies (Gehring et al 2011).…”
Section: Discussionmentioning
confidence: 99%